Normative data and psychometric properties of a farsi translation of the strange stories test. Issue 12 (11th August 2017) - Shahrivar, Zahra; Tehrani‐Doost, Mehdi; Khorrami Banaraki, Anahita; Mohammadzadeh, Azar; Happe, Francesca
Abstract : Background and objective: The Strange Stories test is one of the most commonly used tests to evaluate advanced "theory of mind, " i.e. attribution of mental states. Normative data and psychometric properties of a new Farsi translation of this test were evaluated in a large community‐based sample of Iranian school‐aged children. Methods: Through randomized cluster sampling, 398 children aged 9–11 years studying at 20 elementary schools were recruited from 4 central regions of Tehran, Iran. The mean age of the students was 9.96 years (SD = 0.92), and 51% were girls ( n = 202). The Child Behavior Checklist (CBCL) was completed by parents. The Strange Stories test was completed by all children and repeated for 20% of them after 2–4 weeks to assess the test‐retest reliability. Findings: Students in upper grades had higher scores ( P < .01); age predicted 2% of variance on the mental state score. Girls had significantly higher mentalizing scores than boys ( P = .003). The split‐half internal reliability coefficient was good (0.73). The test‐retest reliability was fair to good. Item‐scale score correlations were all significant ( P < .01). Conclusion: This new translation of the Strange Stories test is a reliable and valid instrument to evaluate higher level theory of mind abilities in community samples of Farsi speaking children. Autism Res 2017, 10: 1960–1967 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: "Mentalizing" or "theory of mind, " the ability to recognize others' mental states, is a key aspect of social understanding. Mentalizing problems are characteristic of some clinical conditions such as autism. The Strange Stories is a test evaluating mentalizing in every day social situations. It was translated into Farsi language and administered to a group of Iranian school‐aged children. The instrument was useful in assessing children's mind reading. Older children and girls were better in mentalizing ability.